SYNTHESIS AND CHARACTERIZATION OF La-DOPED ZnO (La:ZnO) FILMS FOR PHOTODETECTORS - Gozeh, Bestoon Anwer; Karabulut, Abdulkerim; Ameen, Mudhaffer M.; Yildiz, Abdulkadir; Yakuphanoğlu, Fahrettin (World Scientific Publ Co Pte Ltd, 2020)
In this work, the La-doped ZnO thin films were fabricated with different La concentrations by the use of sol-gel technique to synthesize the photodevice. The transparent metal oxide La-doped ZnO thin films were grown on glass and p-Si substrates using spin coating technique. Optical, surface morphology and electrical characterization of the fabricated Al/p-Si/La:ZnO/Al devices have been performed using I-V and C/G-V characteristics under dark and different illumination conditions. Herein, from I-V characteristics, the crucial electronic parameters such as barrier height, ideality factor and series resistance were investigated. The photodevice transient photocurrent increases with the increase of illumination intensity. The current ratios of I-on/I-off were calculated for the fabricated devices. Among the devices, the highest photoresponse was found to be about 2186 for the Al/p-Si/La(0.5 wt.%):ZnO/Al structure. The R-s-V behavior of fabricated device confirms the presence of interface states. The obtained results and photoresponse behaviors suggested that Al/p-Si/La:ZnO/Al devices can enhance the applications in optoelectronic devices such as photodetectors.
Keywords: Electrical characteristics; doped ZnO; sol-gel; photoresponse; photodetector